Visualizing the electric grid. - Overbye, T.J (IEEE spectrum)
In the new world of competition, power traders, grid managers, public service boards, and the public itself all need to take in what's happening at a glance. Visualization software enables viewers to interpret the data more rapidly and more accurately than ever before. This kind of software will become still more useful, even indispensable, as electricity grids are integrated over ever-larger areas, as transmission and generation become competitive markets, and as transactions grow in number and complexity. Concepts like power flow, loop flow, and reactive power, which once mattered only to the engineers directly involved in grid operations, now must be made intuitive. This is because they must be communicated to public service commissions and the consumer-voters to whom such boards are answerable. In short, whether the client/user is a power marketer, a grid operator or manager, a public authority, or a member of the public, power system visualization tools can aid their comprehension by lifting the truly significant above background noise. Such tools can expedite decision-making for congestion management, power trading, market organization, and investment planning for the long term